Empirical evidence of risk shifting in bonds and debt-based sukuk The case of Malaysian corporations - Hamzah, SR; Bacha, OI; Mirakhor, A; Malim, NAK (Emerald Group Publishing Ltd, 2024)
Indexed by WOS/SCOPUS/ERA